Perilaku Nekrofilia Tokoh Robert Mellema dalam Film Roman Bumi Manusia Karya Pramoedya Ananta Toer : Perspektif Psikososial Erich Fromm - Choirul Anam; Siti Qomariyah; Istiqomatul Kholif; Ana Ananda; Fahrur Roziqi (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
In Erich Fromm’s psychosocial, there are constructive instincts (biophilia) and destructive instincts (necrophilia). In the romance film ‘Bumi Manusia’, the psychological elements that looks very contrasting is the necrophilia behavior of the main character Robert Mellema. This qualitative research takes the source from the roman ‘Bumi Manusia’ which is adapted from the phenomenal novel by Pramoedya Ananta Toer (1980). After successfully capturing the attention of many literary art lovers, the same storyline was also made into a film in 2019 with a duration of 3 hours 1 minute. The research data are in the from of quotes from the film ‘Bumi Manusia’ (2019), more specifically about the necrophilia behavior of the character Robert Mellema. In this case, destructive behavior is more interesting to study because it is in line with the reasons for the initation of Erich Fromm’s theory, namely: demeaning others, discriminating, immoral behavior, impolite, addicted to sinful women, and other of destructive behavior.